Sleet and Hail of Verbal Imprecision: Anxiety with the Limits of Logos - Chowdhury, Dr. Piku (Journal of Research in Humanities, 2023)
Whether the words of any literary creation constitute a medium, a representational strategy for grasping the actuality or whether the entire world that can inhere in words is a textual finality, an artificial construct by the words themselves, remains a dilemma unresolved over centuries of debate. Any flicker of faith in the representational or significatory stability of the words can perhaps never suffice and the intellect is bound to face the force of the whirlwinds that blow through any discourse. Eliot’s concern with the word and its communicative efficacy grows out of a long debate laden with intellectual and spiritual perplexities – a debate that arches over the Judeao-Christian and Hellenistic cultures to Aquinas, saint Augustine, Gadamer’s hermeneutics and the modernist speculations. The concept of the logos evolves over centuries passing through spiritual and secular significations and the identity of the word changes with it. T.S. Eliot’s anxiety with the word as a means of poetic communication reveals a chequered journey through a labyrinthine maze of doubt and certitude, laden with the tradition of this age old debate. Whether Eliot reaches the ultimate zone where the transcendental Logos shines out with a luminosity that dispels all doubt, cannot be asserted with exactitude; and pursuing that line of investigation is not part of the present study. The continual unfolding of significatory multiplicities, the inherent tensions and seductions, the intermittent bewilderment and perceptual clarity, that create a brilliant discursive design, are what constitute the essence of his compositions and the thematic crux of this article.